Under One Sceptre, or Mortimer's Mission: The Story of the Lord of the Marches - Holt, Emily Sarah, 1836-1893 (Salt Lake City, UT : Project Gutenberg, 2013)
"Under One Sceptre, or Mortimer's Mission: The Story of the Lord of the Marches" by Emily Sarah Holt is a historical novel written in the late 19th century. The book narrates the tale of Roger Mortimer, an heir of the earldom of March, and contrasts his privileged existence with that of Lawrence, a boy born into servitude. Their intertwined destinies reflect themes of class disparity and the quest for personal significance amidst the rigid social structures of medieval England. The opening of the novel introduces readers to two boys born on the same day in the town of Usk, but from vastly different backgrounds$1 (Bone in the opulence of a castle and the other in the squalor of a mud hovel. The narrative enriches this contrast by illustrating the early lives and aspirations of Roger and Lawrence, as well as their respective families$1 (Battitudes and roles within the feudal system. As they grow, the boys are set on paths that will eventually cross, foreshadowing the complex dynamics of power, loyalty, and ambition that will shape their futures. The beginning sets up a story not just about individual characters, but about the broader societal themes of medieval life and the struggle for justice and freedom. (This is an automatically generated summary.)s
Release date is 2013-12-18
Produced by Al Haines
Keywords: Historical fiction; Mortimer, Roger de, Earl of March, 1328-1360 -- Fiction